The Indian Act and the (Re)Shaping of Canadian Aboriginal Sport Practices - Forsyth, Janice (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2007)
This paper examines how the Indian Act shaped the types of sporting opportunities that were made available for Aboriginal people in the late 19th to the mid-20th centuries. The Indian Act was (and still is) a significant piece of legislation in terms of Aboriginal sport history in that it structured the possibilities for Aboriginal participation in sport in Canada and legitimized Euro-Canadian ways of playing as the most appropriate forms of play.